Research Note: LED chip-on-board packaging technology for strict colour tolerance. (December 2017) - Zhang, J; Ge, P; Zhou, Z; Liu, D; Wang, H; Su, J
In the field of LED packaging, people usually pay more attention to colour temperature, luminous efficacy and colour rendering than colour tolerance. This paper focuses on how to meet strict colour tolerances in the process of chip-on-board packaging. The McAdam ellipses are used to explain the meaning of colour tolerance. A method based on adjusting the amount of phosphor glue and the proportions of different phosphors it contains is described. Measurements on samples packaged according to this method show that it makes it possible to meet strict colour tolerance requirements.